Internal Determinants of Capital Structure of Islamic Banks: Evidence from the Middle East - Abdalla Mohammad Khalaf Al Badarin; Nabeela Khaleel Ibrahim Abanda (Türkiye İslam İktisadı Dergisi)
This study aimed to determine the factors affecting the capital structure of Islamic banks for a sample of the Middle East for the period 2011-2021. The study used a panel data method by pooling ordinary least squares, fixed effects, and random effects to determine the relationship between book leverage and internal variables such as profitability, size, non-debt tax shield, growth opportunity, tangibility, liquidity, and earnings volatility. The descriptive statistics indicate that Islamic banks are highly leveraged. The results of regression showed that the impact of profitability, size, and growth opportunity is positive on book leverage. In contrast, the results indicated a negative impact of non-debt tax shield and liquidity on book leverage. The results also showed no impact of tangibility and earnings volatility on book leverage. Based on the results, Islamic banks in the Middle East enjoy a special method of choosing capital structure depending on their competitive advantage derived from the concentration of a large proportion of Muslim people dealing with them. Nevertheless, the management of Islamic banks must take the mentioned variables into consideration.